Nacionalizmo problema šiuolaikinėje Vakarų istoriografijoje - Pivoras, Saulius (Lietuvos istorijos studijos, 1997)
Historiography in the article is understood in a broad sense, including all major conceptual works devoted to the problem of nationalism during the last decades. Three approaches to the studies on nationalism are outlined: evolutionistic, constructionistic, and phenomenological. Both Anthony D. Smith and Ernest Gellner are characterized as evolutionists. To constructionists in the studies of nationalism, Eric J. Hobsbawm and Benedict Anderson are ascribed. It is argued that the third, phenomenological approach is represented by George L. Mosse, Rogers Brubaker, and Liah Greenfeld. It is asserted that the phenomenological approach is the most legitimate approach from the epistemological point of view. The article ends discussing some categories in Lithuania which, up to this time, have been used in studies of Lithuanian nationalism. They, themselves, have some nationalistic connotations.